Habitat use by Whooper Swans Cygnus cygnus and Bewick’s Swans Cygnus columbianus bewickii wintering in Denmark: increasing agricultural conflicts - Laubek, Bjarke (Wildfowl, 1995)
Coordinated counts of Whooper and Bewick’s Swans were carried out in Denmark during the winter seasons 1991-92, 1992-93 and in January 1992-94. Average numbers in the January counts were 1,130 Bewick’s Swans (c.8% of the flyway population) and 15,800 Whooper Swans (c.63% of the flyway population). Habitat use in Denmark has changed during the past few decades for both species. Previously Whooper and Bewick’s Swans fed mainly in natural habitats, whereas both species in this study (c.80%) fed mainly on farmland. Whooper Swans, in particular, fed on wintergreen crops causing agricultural conflict. Numbers of complaints about swans causing crop damage have increased rapidly since the mid 1980s, a development closely connected to the increase in Danish farming areas with wintergreen crops.